2003
DOI: 10.1038/sj.onc.1206767
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle-dependent phosphorylation of Disabled-2 by cdc2

Abstract: Disabled-2 (Dab2; also known as p96 and DOC-2) is a signal transduction protein that has been implicated in the control of cell growth. Dab2 is known to be a phosphoprotein, but little is known about the kinases that phosphorylate Dab2. We have found that Dab2 phosphorylation is markedly increased during the mitosis phase of the cell cycle. This phosphorylation is blocked by roscovitine, a selective inhibitor of cyclin-dependent kinases. Dab2 robustly coimmunoprecipitates from cells with the cyclin-dependent k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 37 publications
(62 reference statements)
2
27
1
Order By: Relevance
“…The decrease in DAB2 during the luteal phase could partly be explained by altered cdc2 protein levels. Previous studies have indicated that functional BRCA1 indirectly inhibits cdc2 kinase activity (51), which then negatively regulates DAB2 through cell cycle -specific phosphorylation (52). Absence of functional BRCA proteins would therefore lead to accumulation of active cdc2 and subsequent reduction of DAB2.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in DAB2 during the luteal phase could partly be explained by altered cdc2 protein levels. Previous studies have indicated that functional BRCA1 indirectly inhibits cdc2 kinase activity (51), which then negatively regulates DAB2 through cell cycle -specific phosphorylation (52). Absence of functional BRCA proteins would therefore lead to accumulation of active cdc2 and subsequent reduction of DAB2.…”
Section: Resultsmentioning
confidence: 99%
“…In support of this idea, several endocytic proteins including disabled-2 (Dab2), dynamin II (dynII), epsin, eps15, a-adaptin and amphiphysin II, are inactivated by Cdk1-mediated phosphorylation during mitosis (Chen et al, 1999;Chircop et al, 2010;Dephoure et al, 2008;He et al, 2003;Kariya et al, 2000). Furthermore, clathrin, epsin and cyclin-Gassociated kinase (GAK) have been shown to play non-endocytic roles in chromosome alignment and segregation during mitosis (Liu and Zheng, 2009;Royle et al, 2005;Shimizu et al, 2009).…”
Section: Introductionmentioning
confidence: 97%
“…To date, protein kinase C (PKC) and Cdc2 are the only two known DAB2 kinases (14,15). The major PKC phosphorylation site has been mapped to Ser 24 .…”
mentioning
confidence: 99%